Applying Augmented Survey Data to Produce More Accurate, Precise, and Internationally Comparable Estimates of Poverty within the 50 United States - Zachary Parolin (Luxembourg Income Study (LIS), 2017)
This paper introduces a series of augmentations to the Current Population Survey to allow for more accurate estimations of American poverty outcomes and a more fruitful integration of the U.S. into comparative research. The augmentations address three shortcomings in recent poverty research, including (1) severe measurement error in the data from which U.S. poverty estimates are most often derived, (2) the conceptualizations of poverty adopted within U.S.-centric research, and (3) the masking of substantial cross-state variation in poverty outcomes across the 50 United States. Specifically, the augmentations, made public for future researchers to apply, partially correct for the underreporting of four means-tested transfers, establish an internationally comparable conceptualization of poverty, and increase sample sizes for more-precise state-level estimates. The findings illustrate the extent to which prior studies have overestimated the incidence of poverty within the U.S. and have conceptually undervalued the immense heterogeneity of poverty outcomes across the 50 states.
Keywords: I32; D31; J38; 330; poverty; income measurement; CPS ASEC; federalism; comparative social policy